GOVERNMENT POLICY ON SETTLEMENT RELOCATION: A REVIEW OF ITS EVOLUTION AND IMPACT ON INDONESIA - Yohanes, Yulius; Isdairi, Isdairi; Rachmawati, Ida; Magdalena, Julia; Padilah, Ahirul Habib (Department of Government, FISIP, Universitas Padjadjaran, 2025)
Government policies concerning residential relocation are pivotal in urban development, disaster management, and socio-economic transformation. This policy is frequently enacted in Indonesia in response to environmental disasters and urban expansion, yet its effects on the impacted communities remain contentious. This study intends to examine housing relocation policies in Indonesia using a scientometric approach to discern research trends, identify literature gaps, and assess the socio-economic and psychological effects on relocated communities. This study examines the implementation of relocation policies and the factors affecting their success through an analysis of various studies from the Scopus database. The analysis indicates that relocation frequently results in social upheaval, psychological distress, and economic difficulties for the impacted communities. In comparison to global practices, Indonesia's policy approaches continue to encounter obstacles regarding community engagement and the preparedness of supporting infrastructure. Consequently, it is imperative to implement more inclusive and sustainable evidence-based policies to mitigate adverse effects and improve community welfare. This research aims to furnish policymakers with insights for the formulation of more effective relocation programs by thoroughly examining social, economic, and psychological dimensions.gb777